Experimental Study on Unconfined Compressive Strength of Basalt Fiber Reinforced Clay Soil - Lei Gao; Guohui Hu; Nan Xu; Junyi Fu; Chao Xiang; Chen Yang (Advances in Materials Science and Engineering)
In order to study the mechanism and effect of basalt fiber reinforced clay soil, a series of unconfined compressive strength tests conducted on clay soil reinforced with basalt fiber have been performed under the condition of optimum water content and maximum dry density. Both the content and length of basalt fiber are considered in this paper. When the effect of content is studied, the 12 mm long fibers are dispersed into clay soil at different contents of 0.05%, 0.1%, 0.15%, 0.20%, 0.25%, 0.30%, and 0.35%. When the effect of length is researched, different lengths of basalt fibers with 4 mm, 8 mm, 12 mm, and 15 mm are put into soil at the same content of 0.05%. Experimental results show that basalt fiber can effectively improve the UCS of clay soil. And the best content and length are 0.25% and 12 mm, respectively. The results also show that the basalt fiber reinforced clay soil has the “poststrong” characteristic. About the reinforcement mechanism, the fiber and soil column-net model is proposed in this paper. Based on this model and SEM images, the effect of fiber content and length is related to the change of fiber-soil column and formation of effective fiber-soil net.